Association between high expression macrophage migration inhibitory factor (MIF) alleles and West Nile virus encephalitis. (February 2016) - Das, Rituparna; Loughran, Kerry; Murchison, Charles; Qian, Feng; Leng, Lin; Song, Yan; Montgomery, Ruth R.; Loeb, Mark; Bucala, Richard
Highlights: West Nile virus infection is usually asymptomatic but may cause severe encephalitis. The cytokine macrophage migration inhibitory factor is elevated in WNV encephalitis. Patients with high-expression MIF alleles are more likely to have WNV encephalitis. MIF genotype in WNV patients may be useful for prognostic or therapeutic targets. Abstract: Infection with mosquito-borne West Nile virus (WNV) is usually asymptomatic but can lead to severe WNV encephalitis. The innate cytokine, macrophage migration inhibitory factor (MIF), is elevated in patients with WNV encephalitis and promotes viral neuroinvasion and mortality in animal models. In a case-control study, we examined functional polymorphisms in the MIF locus in a cohort of 454 North American patients with neuroinvasive WNV disease and found patients homozygous for high-expression MIF alleles to be >20-fold ( p = 0.008) more likely to have WNV encephalitis. These data indicate that MIF is an important determinant of severity of WNV neuropathogenesis and may be a therapeutic target.